1997
DOI: 10.1097/00005392-199705000-00121
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Collagen Components and Diminution of Nerves in Congenital Ureteropelvic Junction Obstruction

Abstract: In the intrinsic obstruction, nerve fibers were depleted in the muscular layers in the ureteric walls, resulting in dysfunction and atrophy of muscle fibers and an increase of collagen fibers in the muscle layers with abnormal accumulation of intercellular and interstitial collagen. These changes may disrupt the mobility of UPJ and lead to both mechanical and functional obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Surprisingly, in our reviewed CV specimens, we did not find any lower scores for the so-called intrinsic alterations such as muscular hypertrophy, fibrosis, and chronic inflammation. Only few other reports compared histomorphological aspects of ureteral segments in IUPJO with those of CV patients [22][23][24][25]. In most of them, significant differences between IUPJO and CV specimens have been described with fewer or even no intrinsic alterations of the ureteral wall in CV patients [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, in our reviewed CV specimens, we did not find any lower scores for the so-called intrinsic alterations such as muscular hypertrophy, fibrosis, and chronic inflammation. Only few other reports compared histomorphological aspects of ureteral segments in IUPJO with those of CV patients [22][23][24][25]. In most of them, significant differences between IUPJO and CV specimens have been described with fewer or even no intrinsic alterations of the ureteral wall in CV patients [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Only few other reports compared histomorphological aspects of ureteral segments in IUPJO with those of CV patients [22][23][24][25]. In most of them, significant differences between IUPJO and CV specimens have been described with fewer or even no intrinsic alterations of the ureteral wall in CV patients [23][24][25]. However, studies were limited because of very low numbers of analysed patients (four-nine patients) [23,25] or did not deal with paediatric patients [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that abnormalities of innervation of the junction contribute to UPJO [29,30]. Adequate resection of the upper ureter, i.e., at least 8 mm or more beyond the visible lower limit of the constricted segment of UPJ [31], is recommended to prevent reobstruction because of a retained denervated segment.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal nerve innervation patterns and abnormalities of collagen composition, reduction in interstitial cells of Cajal (ICs) and inflammation in the region of stenosis have been demonstrated in previous studies. [2][3][4][5] After Ramon Y. Cajal defined ICs for the first time in the gastrointestinal tract in 1893, Koleda et al [6] have demonstrated the relationship between ICs and UPJO, recently. ICs express a tyrosine kinase receptor c-kit (CD117) on the surface of the cells that is well known by immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%